A Business Paradigm for Corporate Shubh–Labh: An Inquest Study. (December 2017) - Garg, Ruchi; Saluja, Deepika
This study primarily is an inquiry into the business implication of wisdom enshrined in the ancient Indian scriptures for building ethical businesses. This study draws from ethics-related literature and the relationship between kings and subjects from ancient Indian scriptures, to demonstrate the point of convergence and divergence between ancient era and modern management approach for business. The authors suggested three models, namely, Swastika model, "transition from capitalistic to holistic approach, " and trinity model. The models developed in this article forms that foundational basis for the concept of "principles of management" that can be used as basic principles to be adopted by corporate managers. This article concludes with suggestions that would lead us a step further in the direction of creating the Shubh and Mangalam all around.